PENGARUH MODEL PEMBELAJARAN ACTIVE LEARNING TIPE GUIDED NOTE TAKING (CATATAN TERBIMBING) DENGAN PEMANFAATAN LEMBAR KERJA PESERTA DIDIK TERHADAP HASIL BELAJAR SISWA PADA MATERI KEANEKARAGAMAN HAYATI KELAS X MA DDI AT-TAUFIQ PADAELO KABUPATEN BARRU - Fatimah Fatimah; St. Syamsudduha; Jamilah Jamilah (Jurnal Biotek, 2016)
This thesis discusses the influence of the type of learning model Active Learning Guided Note Taking with the use of Worksheet learners to the learning outcomes of students in tenth grade material biodiversity MA DDI AT-Taufiq Padaelo. This study aims to determine student learning outcomes are not using model Active Learning Type Guided Note Taking with the use of worksheets learners, to determine student learning outcomes by using model Active Learning Type Guided Note Taking (Note Guided) with the use of worksheets learners and to examine whether there is influence learning model Active Learning Guided Type Note Taking with the use of worksheets learners on the results of class X student MA DDI AT-Taufiq Padaelo.This research is a Quasi-Experimental Design, using a quantitative approach. The population in this study were all students of class X MA DDI AT-Taufiq Padaelo the academic year 2015/2016. The sampling technique used was saturated sampling technique with a total sample of 42 people. The instrument used was a test. Processing techniques and analyzed using descriptive statistics and inferential analysis.The research showed the average value of student learning outcomes using model Guided Note Taking (Note Guided) with the use of worksheets learners of = 61.67, while the average student learning outcomes that do not use Active learning models Guided Learning Type Note taking (Note Guided) with the use of worksheet learners of = 49.33. The results of inferential analysis of data using SPSS 20 indicates that the value obtained t 3.660> ttabel1,684 and significance (0.001 <0.05). It can be concluded that there is influence learning model Active Learning Guided type Note Taking (Note Guided) with the use of worksheets learners to the learning outcomes of students in tenth grade material biodiversity MA DDI AT-Taufiq Padaelo.